Benign biliary stricture caused by transduodenal lumen-apposing metal stent placement for pancreatic acute necrotic collection - Shuhei Shintani; Takuya Okamoto; Kosuke Hiroe; Hidenori Kimura; Hiroto Inoue; Atsushi Nishida; Osamu Inatomi (International Journal of Gastrointestinal Intervention)
A 58-year-old male patient presented with acute alcohol-induced severe necrotizing pancreatitis. He reported a symptomatic acute necrotic collection in the pancreatic head. No improvements were observed despite one week of antimicrobial therapy. Endoscopic ultrasound-guided drainage via the superior duodenal angle was conducted and a lumen-apposing metal stent (LAMS) was placed. He had an obstructive jaundice progression 3 days postintervention. Endoscopic retrograde cholangiography showed that the cystic side flange of the LAMS caused the distal bile duct smooth stricture. The jaundice improved immediately after the placement of plastic stent in the bile duct, and the LAMS could be removed on the 15th day after placement. The plastic stent was removed after 4 months, and the biliary stricture improved, with no recurrence of jaundice. Here, we report a case of successful conservative treatment of a benign biliary stricture caused by the distal flange of the LAMS.